Syntheses of luciferins and their bioluminescent evaluation - Rylands, Marwaan (Department of Chemistry, 2019)
Luciferins are a class of light emitting small molecule substrates. These molecules are oxidised to produce visible light in a reaction catalysed by the luciferase enzymes. The combination of this luminescent reaction coupled with CCD cameras, has produced revolutionary technologies that enable measurements of mammalian gene expression in cells, as well as protein-protein interactions, biochemical labelling, and small molecule flux, to name a few. Of all the luciferin molecules, D-luciferin is the most widely researched. D-Luciferin is the light emitting molecule isolated from the American firefly Photinus pyralis (Ppy). Synthetic D-luciferin has become increasingly valuable since its incorporation into a growing number of commercially available assays kits, where the molecule is used as a sensitive reporter both in vitro and in vivo. This thesis focuses on improved methods of preparing synthetic D-luciferin and related C6-analogues, as well exploring the bioluminescent properties of a novel C6-thio analogue of D-luciferin. The novel analogue was targeted to provide an alternative or complementary substrate for bioluminescence imaging, that would allow for bioluminescence to be applied in systems where traditional D-luciferin application was limited. In the first part of the thesis, D-luciferin and a C6-amino analogue of D-luciferin, D-aminoluciferin, were prepared using both reported and newly developed procedures. The new methodology afforded the luciferins in improved overall yields and, it was further demonstrated that the new sequence, unlike its palladium-based counterpart, is more scalable, has better functional group tolerability and is relatively greener. The second part of the thesis focuses on the preparation and bioluminescent evaluation of a novel C6- thio analogue of D-luciferin. The new luminogenic substrate, D-thioluciferin, displayed a lower Km and a more red-shifted maximum emission, but with a much lower luminescent output relative to D-luciferin. The thiol handle of D-luciferin and its bioluminescence properties were then explored for potential glutathione reductase (GSR) monitoring, where a D-thioluciferin disulfide was successfully and directly applied to GSR activity sensing. The improved methods of preparation and the novel thioanalogue described in this thesis both contribute to bettering and broadening luciferin-based applications by providing more efficient access to known luciferins, and by increasing the number of luciferin substrate options for bioluminescent research and applications.